Impact of Decentralization on HIV and TB Program Performance in the Rural Central Region of Uganda: The Mediating Role of Decentralized Monitoring and Accountability - Dedrix Stephenson Bindeeba; Semei Christopher Mukama; Rennie Bakashaba; Jane SenyondoNakawesi; Catherine Senyimba; Yvonne Karamagi (World Medical & Health Policy, 2025)
This study examines the impact of decentralization on HIV and Tuberculosis (TB) program performance in rural central Uganda, highlighting the mediating role of decentralized monitoring and accountability (DMA). Decentralization aims to improve service delivery through local governance, yet its effectiveness and underlying mechanisms remain underexplored. A cross‐sectional survey of 145 district leaders overseeing HIV and TB programs across eight districts utilized a structured questionnaire and SPSS Version 27. The reliability of decentralization constructs was verified using Cronbach's alpha, while principal component analysis confirmed their Validity. Five constructs emerged: local resource mobilization (LRM), decen tralized strategic resource allocation (DSRA), decentralized collaborative program governance (DCG), decentralized program administration (DPA), and DMA, alongside HIV and TB Program Performance (HPP). Regression and mediation analyses demonstrated that DSRA and DPA significantly enhanced HPP by promoting equitable resource allocation and administrative efficiency. DMA mediated the effects of DSRA, DCG, and DPA on HPP, reinforcing gains through transparency, reporting, and stakeholder oversight. However, LRM showed no significant direct or mediated impact, implying that fiscal autonomy alone may not drive program success. These findings suggest decentralization can strengthen health outcomes when supported by robust local planning, administrative capacity, and continuous monitoring. Policymakers should channel resources into local governance infrastructure, DMA included, to ensure that decentralized frameworks advance HIV and TB service delivery.
Keywords: Decentralization; HIV and TB programs; Monitoring and accountability; Resource allocation; Uganda